The Effect of Financial Ratio in Financial Distress with Firm Size as Moderated Variables (Empirical Study of Manufacturing Sector Companies Listed on The Indonesia Stock Exchange for The 2014-2018 Period) - Suharti, Suharti; Purnamasari, Yunita; Patria Mahari, Ardhyayuda; Astutik, Menik Puji; Pawiati, Suci (IPTEK Journal of Proceedings Series, 2020)
This study aims to obtain empirical evidence and analyze the effect of financial ratios on financial distress with firm size as a moderating variable. The financial ratios include liquidity ratios that are proxied by Current Ratio, solvency ratios proxied by Debt Asset Ratio, profitability ratios proxied by Return on Assets and Firm Size proxied by the natural logarithm of Total Sales. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange in 2014 - 2018. The total sample used in this study were 85 companies based on established criteria. Data analysis was performed by binary logistic regression and Moderated Regression Analysis. The results of the analysis of this study indicate that the Current Ratio, Debt Asset Ratio and Return on Assets have a significant negative effect on financial distress. The results of the Moderated Regression Analysis reveal that firm size has a significant moderation effect on the relationship between the three independent variables and financial distress in manufacturing companies.